Incidence of suicide among teenagers and young adults in Transkei, South Africa - Banwari L. Meel (AOSIS, 2009)
Background: Transkei is the least developed of the former black homelands in South Africa and has a population of about 4 million. People in this area are poor and depend mainly on the income from migratory workers to the gold mines. Suicide is a complex problem, with no definitive causative agent that has been identified as yet. Suicide among teenagers and young adults is now emerging as an important mental health issue. Suicidal behaviour in the population is under- researched, and therefore under-reported. Method: This is a retrospective record review from 1993 to 2003, carried out in the Umtata General Hospital mortuary. About 1 000 medico-legal autopsies are conducted annually, and the mortuary caters for a population of about 400 000. Results: Of the 10 340 medico-legal autopsies, 398 (3.84%) suicide cases were due to hanging. The number has increased from 5.2 per 100 000 of the population in 1993 to 16.2 in 2003. More than a half (55%) of the hangings were of people less than 30 years of age, and less than one-quarter (23%) of these victims were younger than 20 years. The rate in males has increased from 4.5 (1993) to 14 per 100 000, and in females from 0.7 to 2.2 per 100 000. The male/female ratio is recorded highest (9 : 1) in the 20- and 29-year age group. Conclusion: There is an increasing incidence of suicides among young adults. Suicidal tendency among teenagers and young adults is emerging as an important health issue that needs to be addressed.